An Analytical Survey Study of Arabic Research Dealing with the Guidance of Gifted Students from 2018-2023 - Al Safar, Zainab Abdullah; Al-Arfaj, AbdulHamid Abdullah (Journal of Educational and Psychological Sciences, 2025)
The current study aimed to describe and analyze the content of Arab studies that dealt with guidance in the field of the gifted from 2018 to 2023 AD, in terms of the countries that published the most studies on gifted guidance, the most addressed research objectives, the areas of guidance, the most used methodologies, and the most targeted samples in the published studies. The descriptive analytical method was employed to suit the nature of the study. The study sample consisted of (132) Arab studies. The results showed that the Kingdom of Saudi Arabia, Egypt, and Algeria held the top positions in addressing the field of guidance for the gifted. The majority of the studies aimed to describe phenomena, which constituted 40% of the total published studies, followed by the goal of skill development. Studies on determining the characteristics of standards and services were the least common among the studies. The results also indicated that the field of psychological counseling was the most covered field, at a rate of 43%, followed by academic counseling at a rate of 24%, and professional counseling was the least covered at a rate of 16%. Regarding the methodologies used in the published studies, the descriptive method was the most used at a rate of 49%, followed by the quasi-experimental method at a rate of 31%, while the survey and qualitative methods were the least used. Regarding the samples, the largest group was teenage students in the middle and secondary stages, at 20%, followed by teacher guidance at 14%, studies of counselors at 3%, and parents at 2%, being the least among the published studies. These findings were utilized through the following recommendations: developing targeted guidance programs for children in kindergarten and elementary school, training certified specialists in gifted education, implementing family guidance initiatives and parental awareness campaigns, conducting needs assessment studies to identify required guidance services, prioritizing research related to career guidance strategies, diversifying methodological approaches in gifted education research through qualitative designs, enhancing studies on twice-exceptional individuals (2e), and expanding the scope of university-level guidance interventions for gifted students.
Keywords: content analysis; Survey method; guidance; gifted people